Potentially probiotic fermented glutinous rice (oryza sativa l.) with Lactiplantibacillus plantarum improved immune system response in a small sample of BALB/cByJ mice - Hussin, Muhaini; Anzian, Aliaa; Liew, Crystal Xiao-Qi; Muhialdin, Belal J.; Mohsin, Aliah Zannierah; Fang, Chee-Mun; Saad, Mohd Zamri; Ahmad, Nurul Hawa; Hassan, Masriana; Adnan, Hazniza; Meor Hussin, Anis Shobirin (MDPI, 2022)
L. plantarum strains displayed different abilities to exhibit high survivability to acid (pH 3.0), bile salts (3%), enzyme (pepsin), and temperature (40 °C) and good antibiotic susceptibility. The isolates were further supplemented in traditional tapai pulut to study the immunomodulation properties of tapai pulut based on the splenic T- and B-cell populations. The mice groups were divided into group one (unfermented glutinous rice), group two (tapai pulut group), and group three (probiotic tapai pulut group). Group one showed consistent body weight gain, with the highest observed after four weeks. Group three exhibited the most significant reduction in the percentage of CD19+ B-cells. The CD3+ T-cells population of Group three increased significantly compared with the control mice, followed by Group two. The results suggest that traditional tapai pulut supplemented with L. plantarum has a high potential for supporting the immune system’s immunomodulatory effect.